2022
DOI: 10.1007/978-3-031-06249-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prior Visual Information on Exploratory Movement Direction in Texture Perception

Michaela Jeschke,
Aaron C. Zöller,
Knut Drewing

Abstract: When humans explore objects haptically, they seem to use prior as well as sensory information to adapt their exploratory behavior [1]. For texture discrimination, it was shown that participants adapted the direction of their exploratory movement to be orthogonal to the orientation of textures with a defined direction [2]. That is, they adapted the exploratory direction based on the sensory information gathered over the course of an exploration, and this behavior improved their perceptual precision. In the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We also asked whether this behavior can be further moderated by the quality of the priors and the present task demands, and which mechanism is likely to enable the behavior. Experiment 1 13 demonstrated that indeed, visual priors indicating a texture’s orientation produce orthogonal movement adjustments at initial contact similar to those that typically occur over the course of an exploration 12 . Additionally, it became evident that the higher the priors’ quality, the more pronounced the movement adjustments become.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We also asked whether this behavior can be further moderated by the quality of the priors and the present task demands, and which mechanism is likely to enable the behavior. Experiment 1 13 demonstrated that indeed, visual priors indicating a texture’s orientation produce orthogonal movement adjustments at initial contact similar to those that typically occur over the course of an exploration 12 . Additionally, it became evident that the higher the priors’ quality, the more pronounced the movement adjustments become.…”
Section: Discussionmentioning
confidence: 72%
“…In Experiment 1, we studied the role of information quality for the priors’ usage in haptic frequency discrimination 13 . Participants spent on average 5.5 s ( SD = 1.36) per trial on the stimuli, performed 6.6 strokes ( SD = 2.67), switched 1.7 times ( SD = 0.37) between them and gave 91.1% correct responses ( SD = 8.88%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation